Evaluation of Adulticidal Efficacy of Cypermethrin, Tetramethrin, and Piperonyl Butoxide in Housefly (Musca Domestica) - Licup, Bianca Patricia E.; Purnamasari, Listya; Olarve, Joseph Penano; dela Cruz, Joseph Flores (Universitas Airlangga, 2024)
Introduction: Houseflies serve as vectors of diseases in animals and humans. Chemical pesticides are a practical way of eliminating insects; however, resistance to insecticides has been reported. This study aims to evaluate the adulticidal efficacy of cypermethrin, tetramethrin, and piperonyl butoxide in housefly. Methods: Adult flies were cultured within net enclosures using completely randomized design with four replications each treatment. Treatment A was water and served as the negative control, treatment B was cypermethrin + tetramethrin + piperonyl butoxide 32% EC and served as the positive control, and treatment C was cypermethrin + tetramethrin + piperonyl butoxide 48% EC. The number of dead houseflies were counted 15, 30, 60, and 120 minutes post- application of treatments. The results were analyzed through analysis of variance (P≤0.05) followed by Tukey’s HSD (honestly significant difference). Results and Discussion: The values for the cumulative mean and percentage of killed houseflies were all significantly different from each other, with treatment C showing the highest values, followed by treatment B, then treatment A. The maximum adulticidal effect of treatment C was apparent within 15 minutes post-application, while the maximum adulticidal effect of treatment B was observed within 30 minutes after application. Conclusion: Results suggest that treatment C was a more effective adulticidal than other groups. Using cypermethrin + tetramethrin + piperonyl butoxide 48% EC can be the solution to the problem, but it should be noted that future resistance may occur. Increased concentrations may also imply environmental, human, and animal health hazards.